Successful Pulmonary Endarterectomy in a Patient with Klinefelter Syndrome - E. Wierda; H. J. Reesink; H. Bruining; O. M. van Delden; J. J. Kloek; P. Bresser (Case Reports in Pulmonology)
Klinefelter syndrome (KS) is a frequent genetic disorder due to one or more supernumerary X chromosomes. KS is associated with an increased risk for venous thromboembolic events like deep venous thrombosis and pulmonary embolism. This paper describes a 37-year-old male patient with KS referred to our tertiary center with chronic thromboembolic pulmonary hypertension, and who was successfully treated by pulmonary endarterectomy.